Juridical analysis of a sale and purchase binding agreement on land - Nadhirawaty Nadhirawaty; Soerya Respationo; Erniyanti Erniyanti; Ramon Nofrial; Fadlan Fadlan (Annals of Justice and Humanity, 2022)
Purpose: The purpose of this research is to find out the legal arrangement of the agreement of binding sale and purchase of land, to find out the legal consequences of the implementation of the issuance of the agreement of binding sale and purchase of land by Notary in Batam City. Research Methodology: The research method of this thesis is normative juridical (legal reasearch) through literature study with empirical juridical (sociological juridical) approach through field study which aims to obtain legal knowledge empirically. Results: The results show that the legal regulation of the Sale and Purchase Agreement on land in Indonesia underlines the importance of the role and function of notaries, as well as the position of Sale and Purchase Binding Agreement as an important legal instrument in land sale and purchase transactions. Implementation: The Sale and Purchase Binding Agreement has the legal power to bind both parties and serves as the basis for the implementation of the transaction, proof of the transaction, a means of dispute resolution, and a legal protection tool for both parties. The legal consequences of the issuance of a Sale and Purchase Agreement on land by a Notary in Batam City are very important in determining the sustainability of property transactions in the area. With a thorough verification and validation process, as well as checking documents and providing objective and accurate legal advice by a notary, the sustainability and validity of the transaction can be better guaranteed, and the rights and obligations of each party can be better protected.